Seychelles : Fourth Review Under the Policy Coordination Instrument and Request for Modification of Targets. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Seychelles' Fourth Review Under the Policy Coordination Instrument (PCI) and Request for Modification of Targets. Economic developments since the completion of the 2019 Article IV consultation and the third review under the PCI in June 2019 have been broadly in line with expectations. The program is largely on track. The 2020 budget recently submitted to the National Assembly is in line with the program and the major infrastructure and climate change related projects would be implemented within the fiscal parameters under the PCI. All quantitative targets for end-June 2019, the program's fourth review test date, were met except for the primary fiscal surplus target, which was missed by a very small margin due to a delay in receipts from 2016 to 2017 sales of a telecom company. The economic outlook continues to be favorable. Downside risks to the outlook largely stem from possible external shocks, including weakness in the key tourism markets and global banks' withdrawal of correspondent banking relationships.